EL ROL DE LAS MUJERES EN EL ÁMBITO PROFESIONAL DE LAS RR. PP. EN LA ARGENTINA (Hologramática, 2023)
Within the framework of the project developed at the Faculty of Social Sciences of the National University of Lomas de Zamora on "Transdisciplinary approaches in the Social Sciences in the approach to gender issues", where 8 teams worked articulately on lines that link different issues raised from the different undergraduate disciplines taught at the Faculty.To address these phenomena, the contribution of Edgar Morin's Theory of Complexity was taken, adopting the transdisciplinary methodology to articulate and discuss different points of view that provide diverse perspectives on the problems associated withgender issues that by definition do not admit simple or linear explanations.In this sense, this article presents some of the qualitative results of one of the investigations that were part of the project. Since there is no specific data on the subject of Public Relations in Argentina, it is hoped that these results can provide information to understand the situation of women in this field in relation to the "glass ceiling".Although qualitative results will be discussed, a qualitative-quantitative methodology has been used, where more than 250 surveys (random, non-probabilistic) and 17 in-depth interviews with leading Public Relations professionals in Argentina have been analyzed.
Keywords: Gender; stereotypes; Glass Ceiling; Public Relations